Implementation and Monitoring of a Gestational Trophoblastic Disease Management Program in a Tertiary Hospital in Morocco: Opportunities and Challenges - Imane Khachani; Mohamed Hassan Alami; Rachid Bezad (Obstetrics and Gynecology International)
Objective. Gestational Trophoblastic Disease (GTD) management requires clear guidelines for diagnosis, treatment, and follow-up. Unequal management skills among practitioners, inadequate treatment, irregular surveillance, and drop-out are common in resource-limited settings and can lead to life-threatening complications and morbidities. To address these challenges, we implemented a GTD Management Program at the National Center for Reproductive Health in Rabat, Morocco. Methods and Program Description. In-depth review of management protocols was carried out, and concise guidelines were developed, with targeted training for physicians. A physical space and a weekly fixed GTD consultation were set, and personalized follow-up was established for each patient. An electronic database documenting patients’ surveillance was created, allowing immediate outreach in case of irregularities. Results. During the period from October 2013 to June 2016, 50 patients were included in this program. Patients’ mean age was 33 years; 92% were illiterate and 82% had a low socioeconomic status. 68% had a positive evolution, while 32% developed gestational trophoblastic neoplasia, requiring 2 to 6 chemotherapy sessions. An average of 2.8 outreach reminders were necessary for each patient. 94% fully adhered to the program of care and completed properly their follow-up. Conclusion. Implementation and thorough monitoring of this program helped optimize patients’ care, avoiding drop-outs and delays in diagnosing and treating complications.